Infective Endocarditis After Melody Valve Implantation in the Pulmonary Position: A Systematic Review. Issue 13 (3rd July 2018) - Abdelghani, Mohammad; Nassif, Martina; Blom, Nico A.; Van Mourik, Martijn S.; Straver, Bart; Koolbergen, David R.; Kluin, Jolanda; Tijssen, Jan G.; Mulder, Barbara J. M.; Bouma, Berto J.; de Winter, Robbert J.
Abstract : Background: Infective endocarditis (IE) after transcatheter pulmonary valve implantation (TPVI) in dysfunctioning right ventricular outflow tract conduits has evoked growing concerns. We aimed to investigate the incidence and the natural history of IE after TPVI with the Melody valve through a systematic review of published data. Methods and Results: PubMed, EMBASE, and Web of Science databases were systematically searched for articles published until March 2017, reporting on IE after TPVI with the Melody valve. Nine studies (including 851 patients and 2060 patient‐years of follow‐up) were included in the analysis of the incidence of IE. The cumulative incidence of IE ranged from 3.2% to 25.0%, whereas the annualized incidence rate ranged from 1.3% to 9.1% per patient‐year. The median (interquartile range) time from TPVI to the onset of IE was 18.0 (9.0–30.4) months (range, 1.0–72.0 months). The most common findings were positive blood culture (93%), fever (89%), and new, significant, and/or progressive right ventricular outflow tract obstruction (79%); vegetations were detectable on echocardiography in only 34% of cases. Of 69 patients with IE after TPVI, 6 (8.7%) died and 35 (52%) underwent surgical and/or transcatheter reintervention. Death or reintervention was more common in patients with new/significant right ventricular outflow tract obstruction (69% versus 33%; P =0.042) and in patients with non‐streptococcal IE (73% versus 30%; P =0.001). Conclusions: The incidence of IE after implantation of a Melody valve is significant, at least over the first 3 years after TPVI, and varies considerably between the studies. Although surgical/percutaneous reintervention is a common consequence, some patients can be managed medically, especially those with streptococcal infection and no right ventricular outflow tract obstruction.